Utilization Of Social Media As A Health Promotion Tool For Hospitals in Indonesia: Literature Review - Cut Roza Asminanda; Solihin Solihin; Murni Noviani; Balqis Nurmauli Damanik (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The use of social media in various aspects including health has increased in recent years. The effectiveness and efficiency of the use of social media in health promotion efforts by hospitals are advantages compared to using conventional media. This study aims to obtain information about the use of social media by hospitals in efforts to organize hospital health promotion from the perspective of: 1) types of social media used, 2) program effectiveness, 3) level of involvement, and 4) efforts to increase the level of involvement. From a search of 62 articles (time span 2017-2022) using the Google Scholar and Garuda databases and the keywords media, social, hospital, promotion, and health, researchers found 3 articles that were appropriate based on the title, abstract, content and purpose of the study. This literature study revealed that social media has high effectiveness and efficiency in organizing health promotion programs by hospitals. Another finding is that Instagram is the most widely used social media platform with the highest level of involvement compared to other social media platforms. Interesting and unique efforts and strategies can further increase the level of public involvement in hospital social media accounts so that there is an increase in awareness of healthy living in Indonesian society.